Ciberenterprising in groups and virtual social networks in the PostIndustrial Technological Cibersociety (PTC) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The creation of social virtual networks has been stimulated by the appearance of a new type of entrepreneur that we might call, given his peculiarities: group cyberentrepreneur.This fact is transforming the society and in the company of the 21st century it is opening new possibilities of business inside the digital economy. The democratization of the TIC and the major knowledge and skills acquired by the internauts is accelerating the above mentioned process of transformation that is taking place (produced) inside the Technological Post-industrial Cyber-society (CTP). In this work there are analyzed which are the characteristics of these social virtual networks, as well as the cyber-entrepreneur is defined and characterized.
Keywords: Entrepreneurship; social network; ITC; knowledge; globalization